Pengenalan Bisnis Kopi Kayu Manis kepada Mahasiswa Akademi Komunitas Presiden - Abdul Ghofir; Genta Sahuri Sahuri; Dedi Rianto Rahadi (President University, 2020)
Coffee is a mandatory drink for some people, both man and woman. It is very delicious to be enjoyed, especially in the morning before the move, or during rush hours at work. Coffee is like a friend whose always present in any condition. Increasing coffee trends make the coffee business increasingly widespread. Many ways have been done by people to do coffee business. Ranging from simple coffee business such as street vendors to starred restaurant. High competition makes the coffee business must be good in innovating. Armed with the ability to mix coffee, then a number of students and lecturers of President University Majoring in Management made an idea to mix coffee with cinnamon. The concoction of cinnamon coffee is simply packaged 250 ml plastic bottle, which is then sold at very affordable prices both online and offline. The ability to mix and do cinnamon coffee business is then transmitted to other communities, that is the students of Akademi Komunitas Presiden. The principle is sharing, sharing knowledge, sharing experience, and sharing cheerful.Keywords: Coffee, Cinnamon, Business, Industry.